Karakteristik Tepung Sukun (Artocarpus Altilis) - Hendrawan, Hendrawan (Ma'soem University, 2024)
Breadfruit besides can be consumed directly, can also be processed into intermediate product, that is processed into breadfruit flour. Producing breadfruit flour is an effort of food diversification, to reduce people dependency on wheat flour, and to extend the storage time. Characteristic of Breadfruit flour is affected by temperature and drying time. Therefore, it is necessary to do research to find out the effect of drying time on particular temperature level on characteristic of breadfruit flour. This research applied the Randomized Block Design with five treatments which was drying time (A: 6, B: 6.5, C: 7, D: 7.5, E: 8 hours), and each treatment was repeated five times. The organoleptic test was conducted on color and aroma, while the chemical test was moisture content. Result of the research showed that drying time effected color and moisture content significantly. However, aroma was not affected by the drying time. The best characteristic was produced by treatment A (6 hours) based on color (4.85). moisture content of the product was 12.21%.